2007
DOI: 10.1037/0022-3514.93.1.23
|View full text |Cite|
|
Sign up to set email alerts
|

The magic spell of language: Linguistic categories and their perceptual consequences.

Abstract: Language is a tool that directs attention to different aspects of reality. Using participants from the same linguistic community, the authors demonstrate in 4 studies that metasemantic features of linguistic categories influence basic perceptual processes. More specifically, the hypothesis that abstract versus concrete language leads to a more global versus local perceptual focus was supported across 4 experiments, in which participants used (Experiment 1) or were primed either supraliminally (Experiments 2 an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
50
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(54 citation statements)
references
References 62 publications
4
50
0
Order By: Relevance
“…Our perceptual processes may also be affected by culturally characteristic physical environment (Miyamoto, Nisbett, and Masuda 2006). Further, linguistic theories posit that language produces fundamental differences in thought, memory, attention, and perception across cultures (Stapel and Semin 2007). Therefore, even though warmth is a universal basic human need (Maslow 1943), culture might exert another layer of influence on the physical-psychological warmth link through our interaction with the physical environment and language afforded by culture.…”
Section: Discussionmentioning
confidence: 98%
“…Our perceptual processes may also be affected by culturally characteristic physical environment (Miyamoto, Nisbett, and Masuda 2006). Further, linguistic theories posit that language produces fundamental differences in thought, memory, attention, and perception across cultures (Stapel and Semin 2007). Therefore, even though warmth is a universal basic human need (Maslow 1943), culture might exert another layer of influence on the physical-psychological warmth link through our interaction with the physical environment and language afforded by culture.…”
Section: Discussionmentioning
confidence: 98%
“…The results of the study indicated that the global condition, compared to the local condition, generated more unusual category exemplars. The effect of conceptual processing on perceptual processing was also demonstrated in a study by Stapel and Semin (2007). In this study, participants were primed to a high-level construal (using adjectives), versus a low-level construal (using concrete verbs).…”
Section: Discussionmentioning
confidence: 99%
“…The content of more abstract, higher level construals consist of the perceived gist, essence, or summary of the given information about events and objects, whereas the content of lower level, more concrete construals consist of context-dependent, readily observable features of events and objects (Medin & Ortony, 1989;Schul, 1983). The process that results in higher level construals involves broad and global consideration of information about events and objects, whereas the process that results in lower level construals involves narrow and localized consideration of information about events and objects (Liberman & Förster, 2009;Stapel & Semin, 2007).…”
Section: A Construal Level Theory Of Physical Distancementioning
confidence: 97%